2021
DOI: 10.1126/scitranslmed.abb4582
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of leukocyte trafficking kinetics in macaques by serial intravascular staining

Abstract: Leukocyte trafficking enables detection of pathogens, immune responses, and immune memory. Dysregulation of leukocyte trafficking is often found in disease, highlighting its important role in homeostasis and the immune response. Whereas some of the molecular mechanisms mediating leukocyte trafficking are understood, little is known about the regulation of trafficking, including trafficking kinetics and its impact on immune homeostasis. We developed a method of serial intravascular staining (SIVS) to measure tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 39 publications
4
30
1
Order By: Relevance
“…Using intravenous (i.v.) antibody staining to distinguish between tissue parenchymal and intravascular cells [73][74][75] , we confirmed that most cells in the BAL, nasal turbinates, salivary gland, tonsils, and lymph nodes were from the tissue parenchyma (Fig S5). As expected for such a highly vascularized tissue, most cells from the lung tissue were intravascular stain positive, but a small population of CD69 + ivcells were detectable in the lungs confirming that tissue resident cells were also detected in pulmonary tissue.…”
Section: Distribution Of Sars-cov-2-specific Cd8 and Cd4 T Cell Responses In Mucosal Tissuessupporting
confidence: 62%
“…Using intravenous (i.v.) antibody staining to distinguish between tissue parenchymal and intravascular cells [73][74][75] , we confirmed that most cells in the BAL, nasal turbinates, salivary gland, tonsils, and lymph nodes were from the tissue parenchyma (Fig S5). As expected for such a highly vascularized tissue, most cells from the lung tissue were intravascular stain positive, but a small population of CD69 + ivcells were detectable in the lungs confirming that tissue resident cells were also detected in pulmonary tissue.…”
Section: Distribution Of Sars-cov-2-specific Cd8 and Cd4 T Cell Responses In Mucosal Tissuessupporting
confidence: 62%
“…In our liver sample, most NK cells were IVas+, which was expected given that the liver contains primarily sinusoidal capillaries. The liver IVas+ cells had a distinct NK phenotype from blood cells in the same animal (Figure S4A), indicating that a large fraction of NK cells in liver may occupy a perivascular niche, as previously reported for T cells in the liver (38). Within our lung sample, the majority of DN and CD16 NK cells were IVas+, while the majority of CD56 NK cells were IVas-, indicating a possible difference in localization within lung tissue (Figure S4B).…”
Section: Nk Subsets Show Differential Trafficking Kinetics Into Lymph Nodes and Other Tissuessupporting
confidence: 82%
“…The National Institutes of Health (NIH) and Bioqual Inc. (where some animals were housed) are accredited by the Association for Assessment and Accreditation of Laboratory Animal Care and are in full compliance with the Animal Welfare Act and Public Health Service Policy on Humane Care and Use of Laboratory Animals. Sedation and euthanization followed previously described protocols ( 38 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using our virtual population of 500 hosts, we are able to show that early events at both granuloma-and host-scales can be predictive of clinical-scale outcomes ~150 days later (at 200 days p.i.). These predictions are potentially useful for experimentalists, who can use analogous experimental techniques (such as serial intravascular staining (95), or IHC cytokine staining of granulomas ( 96)) to make educated predictions about downstream clinical-scale outcomes. Further, these HostSim predictions contribute to a growing body of evidence that suggests early immune events matter in TB (15,82,97).…”
Section: Discussionmentioning
confidence: 99%